(untitled) (International Journal of Biomedical Research, 2015)
A number of studies have investigated the roles of lipid peroxidation/ anti-oxidative balance as risk factors of prostate cancer. However, no study has yet to relate these factors with dietary habits of individuals in this environment. The objective of this study was to assess the role of lipid peroxidation and its relationship with vitamin D, calcium and dietary habits in individuals with prostate cancer. A total of sixty four (64) male participants (32 patients and 32 age-matched apparently healthy individuals as control) were recruited. Blood samples were analyzed for Malondialdehyde (MDA), Total antioxidant status (TAS), Calcium and Albumin spectrophotometrically; Prostate specific antigen (PSA) using immune radiometric assay; and Vitamin D by high performance liquid chromatography. Participants with prostate cancer had a significantly higher (p? 0.05) mean plasma level of MDA and PSA but lower TAS and vitamin D when compared with the control group. The plasma levels of MDA had a significant positive correlation with plasma PSA while negative with TAS in both groups. A significant proportion of the study participants that consumed dairy and smoked food regularly had a higher mean plasma level of MDA when compared with those that did not regularly as well as the control. This study has provided support for the hypothesis that lipid peroxidation and oxidative stress is associated with prostate cancer. A peculiar relationship exists between dairy and smoked food in prostate cancer which may be linked with increased lipid peroxidation.